A layered coating for precision casting shell and a preparation method thereof
By selectively selecting and optimizing the organic reinforcing phases of the surface layer, transition layer, and back layer in a low-sodium silica sol binder system, and combining this with a stepwise in-situ curing process, the problem of insufficient performance of layered coatings in existing technologies has been solved, achieving the effects of high density and erosion resistance of the shell, high bonding and peel resistance of the transition layer, and high strength of the back layer.
Patent Information
- Application Number
- CN202611260145.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-11-06
AI Technical Summary
In the existing technology, the layered coating design fails to make targeted selection and ratio optimization of organic reinforcing phase according to the functional requirements of the top layer, transition layer and back layer, resulting in the shell performance failing to meet the requirements of high density and erosion resistance, high bonding and peel resistance of the transition layer and high strength of the back layer.
Under the same low-sodium silica sol binder system, based on the functional differences of the top layer, transition layer and back layer, the organic reinforcing phase is selected and optimized, and combined with the stepwise in-situ curing process, so that each coating layer forms a stable organic-inorganic hybrid structure, thereby achieving synergistic performance improvement.
It improves the overall performance of the shell, including high surface hardness and low residual carbon in the surface layer, high wet strength and air permeability in the back layer, and good interlayer bonding in the transition layer, making it suitable for precision casting of high-temperature alloys and stainless steel.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of precision casting technology, specifically relating to a layered coating for precision casting shell making and its preparation method. Background Technology
[0002] Silica sol investment casting is an important method in the field of precision casting for producing complex shapes and high-precision castings, and it is widely used in aerospace, medical devices, and high-end equipment manufacturing. This process uses silica sol as a binder and has advantages such as being environmentally friendly, low-cost, and having high high-temperature strength. With the development of organic polymer materials, modifying silica sol with organic polymers to balance the high-temperature performance of the inorganic phase and the wet toughness of the organic phase has become an important technical route in the industry.
[0003] In the area of polymer-modified silica sol, existing technologies have been extensively explored. US Patent 7128129B2 discloses a colloidal silica containing 3% latex for investment casting shell production, utilizing the elasticity of the latex to prevent shell cracking during curing and increasing brushability. Chinese Patent CN106232261B discloses an investment casting composition in which the organic binder can be a mixture of colloidal sol and acrylic latex polymers, including styrene-butadiene latex. Another Chinese patent application, CN111790881A, discloses an organic reinforcing agent for modified precision casting silica sol, which is a compound of acrylic emulsions, butadiene latexes (including styrene-butadiene latex, nitrile latex, etc.), waterborne polyurethane emulsions, and VAE emulsions, used to improve the drying speed and wet strength of the silica sol film and reduce residual strength. The embodiments specifically disclose a scheme using a compound of styrene-acrylic latex, nitrile latex, and styrene-butadiene latex as the organic reinforcing agent. At the industrial product level, Guangdong Huierte Nanotechnology Co., Ltd. has developed the SKP27-3 type surface layer reinforced silica sol, which is modified by adding organic binders (containing amino polymers) to the silica sol to improve wet strength and shorten drying time; the fast-drying precision casting silica sol, after adding polymers, has a faster wet strength build-up speed, a significantly shorter drying time, and a significantly improved yield.
[0004] In the current field of layered coating design, existing technologies mainly focus on differentiating the types of refractory aggregates or binders, rather than differentiating the organic reinforcing phases for the functional requirements of each layer within the same silica sol binder system. For example, patent CN105108053B discloses a surface coating for precision casting shells, using silica sol, zircon powder, wetting agent, and defoamer as raw materials; patent CN105108054B discloses a transition layer coating for precision casting shells, also based on silica sol and zircon powder, with only the ratio of defoamer and wetting agent optimized. Patent application CN116851640A discloses a turbine mold shell and its preparation method, where the surface layer, transition layer, and back layer are distinguished only by the type of refractory aggregate (cobalt aluminate, zircon powder, zircon sand, etc.), and the binder for each layer is ordinary silica sol. Patent application CN101642798A discloses a composite coated shell, in which the surface layer uses a ethyl silicate-silica sol mixed adhesive and the back layer uses a water glass adhesive, representing the layered use of different types of adhesives. US patent US10953460B2 discloses an investment casting back coating that uses a polymer emulsion as a thixotropic agent, but does not address the polymer reinforcement design of the surface and transition layers.
[0005] In summary, existing polymer-modified silica sol technologies are mostly general-purpose formulations, employing a single organic reinforcing agent or polymer emulsion for multiple layers of the shell. They fail to address the inherent functional differences between the surface layer, transition layer, and back layer by selectively choosing and optimizing the proportions of the organic reinforcing phase. Furthermore, existing layered coating technologies either differentiate between refractory aggregates or use different types of binders. There are no reports of differentiated design of the organic reinforcing phases for each layer within the same silica sol binder system, based on the functional requirements of a high-density, erosion-resistant surface layer, a high-bonding, peel-resistant transition layer, and a high-strength back layer. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides a layered coating for precision casting shells and its preparation method. By using the same low-sodium silica sol binder system, the organic reinforcing phase is selectively chosen and its proportion is optimized based on the functional differences of the surface layer, transition layer, and back layer. Combined with a stepwise in-situ curing process, each coating layer forms a stable organic-inorganic hybrid structure before coating, thereby achieving a synergistic improvement in the overall performance of the shell.
[0007] To achieve the above-mentioned technical objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a layered coating for precision casting shell making, comprising separately packaged topcoat, transition coating, and backcoat, wherein: The topcoat uses low-sodium silica sol as an inorganic binder and carboxylated nitrile latex as an organic reinforcing phase. The amount of carboxylated nitrile latex added is 2-4% of the mass of SiO2 in the low-sodium silica sol, based on dry solids. The transition layer coating uses low-sodium silica sol as an inorganic binder and a compound of styrene-butadiene latex and carboxylated nitrile butadiene latex as an organic reinforcing phase. The mass ratio of styrene-butadiene latex to carboxylated nitrile butadiene latex is (1.5-2.5):1, and the total amount added, based on dry solids, is 4-6% of the mass of SiO2 in the low-sodium silica sol. The back coating uses low-sodium silica sol as an inorganic binder and styrene-butadiene latex as an organic reinforcing phase. The amount of styrene-butadiene latex added is 6-10% of the mass of SiO2 in the low-sodium silica sol, based on dry solids. Among them, the low-sodium silica sol contains Na + Content ≤150ppm, pH 8.5-10.5.
[0008] This invention employs a layered coating system. The carboxyl-based nitrile butadiene latex molecular chain contains polar nitrile and carboxyl groups, exhibiting good compatibility with silica sol. After film formation, it boasts high hardness and excellent oil and chemical resistance, making it suitable for the top layer, which requires high surface hardness and erosion resistance. However, its addition amount should not be too high; otherwise, excessive residual carbon after high-temperature baking may lead to carburization on the surface of cast steel parts. Styrene-butadiene latex has good flexibility and strong film-forming properties. High addition amounts can significantly improve wet strength, making it suitable for the back layer, which requires high wet strength and good air permeability. During baking, the organic components decompose, forming pores in the back layer and improving air permeability and collapsibility. The transition layer uses a blend of both, retaining both affinity with the carboxyl-based nitrile butadiene latex in the top layer and the styrene-butadiene latex in the back layer, which is beneficial for improving interlayer bonding and reducing delamination and peeling.
[0009] In addition, conventional silica sol contains Na + The content is usually between 2000-3000 ppm, with a large amount of Na. + Latex particles exist in a free or adsorbed state on the surface of silica sol particles, leading to a decrease in the absolute value of the surface zeta potential and a compression of the electrical double layer thickness, making it difficult for latex particles to form a stable adsorption layer on the surface of silica sol particles. This invention uses Na... + Low-sodium silica sol with a concentration of ≤150 ppm exhibits a significantly higher density of silanol hydroxyl groups on its surface compared to conventional silica sol, forming a more stable negatively charged double layer under pH conditions of 9.0-9.5. When carboxylated nitrile butadiene latex or styrene-butadiene latex is added, latex particles can selectively adsorb onto the silica sol particle surface through hydrogen bonding and dipole-dipole interactions between silanol hydroxyl groups and polar groups on the latex surface.
[0010] More preferably, the organic base is selected from one or more of N,N-dimethylethanolamine, triethylamine, and diisopropylethylamine, with N,N-dimethylethanolamine being the most preferred.
[0011] N,N-Dimethylethanolamine (DMEA) has a pKa of 9.7, which can stably adjust the pH of the system to 9.0-9.5. Furthermore, the DMEA molecule contains both tertiary amine and hydroxyl groups. The hydroxyl groups can form hydrogen bonds with the carboxyl groups of carboxylated nitrile latex and the residual emulsifiers in styrene-butadiene latex, acting as "molecular bridges" and promoting the selective adsorption of latex particles on the surface of low-sodium silica sol.
[0012] More preferably, the surface coating further includes zircon powder and / or fused alumina powder as refractory aggregate, with a powder-to-liquid ratio of (2.5-3.5):1.
[0013] More preferably, the transition layer coating further includes zircon powder and / or mullite powder as refractory aggregate, with a powder-to-liquid ratio of (2.0-3.0):1.
[0014] More preferably, the backing coating further includes mullite powder and / or quartz sand as refractory aggregate, with a powder-to-liquid ratio of (1.5-2.5):1.
[0015] The selection of refractory components in each layer of the coating of this invention is highly matched with the type of latex. Specifically, the top layer uses high-hardness zircon powder and / or fused alumina powder as aggregate, which works synergistically with the high hardness of carboxylated nitrile rubber latex to form a highly dense and highly erosion-resistant surface layer. The back layer uses mullite powder and / or quartz sand as aggregate, and its porous or layered structure works synergistically with the porous skeleton formed after the styrene-butadiene latex is calcined to further enhance air permeability. The transition layer uses zircon powder and / or mullite powder as aggregate, and its coefficient of thermal expansion is between that of the high-hardness aggregate in the top layer and the porous aggregate in the back layer. This works synergistically with the gradient modulus distribution of the compound latex to reduce interlayer thermal stress.
[0016] More preferably, the carboxylated nitrile butadiene latex has a solid content of 40-50% and a pH of 7.5-8.5; the styrene-butadiene latex has a solid content of 45-55% and a pH of 8.0-9.0.
[0017] Carboxylated nitrile butadiene latex has a slightly lower pH than silica sol, making its addition less likely to cause drastic pH fluctuations in the system. Styrene-butadiene latex has a pH close to that of silica sol, resulting in good compatibility during mixing. The selection of a specific solids content range ensures that the amount of latex moisture introduced is controllable when the target addition amount is reached, avoiding excessive dilution of the silica sol and subsequent decrease in binder concentration. The selection of these latex parameter ranges significantly improves its mixing stability with silica sol.
[0018] Secondly, the present invention provides a method for preparing a layered coating for precision casting shell making, comprising the following steps: Topcoat pre-preparation: Preheat low-sodium silica sol to 35-45℃, and slowly add carboxylated butadiene-acrylonitrile latex pre-dispersion solution dropwise under shear stirring, with the dropwise addition time controlled at 15-30 min; after the dropwise addition is completed, keep the temperature at 30-40℃ for 1-2 h to allow the latex particles to be adsorbed in situ on the silica sol surface; after the curing is completed, add refractory aggregates and additives, and adjust the pH to 9.0-9.5 with sodium-free organic alkali; Pre-preparation of transition layer coating: Preheat low-sodium silica sol to 35-45℃, first add styrene-butadiene latex pre-dispersion, shear and stir for 10-15 min, then slowly add carboxyl-based nitrile-butadiene latex pre-dispersion, controlling the adding time to 10-20 min; after the addition is complete, maintain a constant temperature of 30-40℃ for 1.5-2.5 h; after the curing is complete, add refractory aggregates and additives, and adjust the pH to 9.0-9.5; Backing coating pre-preparation: Preheat low-sodium silica sol to 35-45℃, and slowly add styrene-butadiene latex pre-dispersion solution dropwise under shear stirring, controlling the dropwise addition time to 20-40 minutes; after the dropwise addition is complete, maintain a constant temperature of 30-40℃ for 2-3 hours; after aging, add refractory aggregates and additives, and adjust the pH to 9.0-9.5. More preferably, the shearing and stirring rate in each step is 500-1500 rpm.
[0019] More preferably, during the curing process described in each step, the viscosity is sampled and tested every 30 minutes, and curing is considered complete when the viscosity increase is ≤5%.
[0020] Thirdly, the present invention provides a method for preparing a precision casting shell, which uses the above-mentioned coating system to sequentially coat a surface layer, a transition layer and a back layer, and dries each layer after coating, wherein the drying time of the surface layer is ≤4h, the drying time of the transition layer is ≤6h and the drying time of the back layer is ≤8h.
[0021] Fourthly, the present invention provides a precision casting shell obtained by the above method.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention breaks through the existing technical approach of using general-purpose organic reinforcing agents simultaneously in all layers of the mold shell. Under the same low-sodium silica sol binder system, the organic reinforcing phases of each layer are specifically selected and their proportions optimized based on the functional requirements of the surface layer, transition layer, and back layer. The surface layer uses a low-addition amount of carboxylated nitrile latex, balancing high surface hardness and low residual carbon; the back layer uses a high-addition amount of styrene-butadiene latex, balancing high wet strength and good air permeability; the transition layer uses a blend of both to improve interlayer bonding and reduce interlayer delamination. Combined with a step-by-step in-situ curing process, the storage stability and coating performance of the slurry are improved. Furthermore, the entire system uses low-sodium silica sol masterbatch and adjusts the pH with a sodium-free organic alkali, avoiding the introduction of sodium ions, which is beneficial for improving the high-temperature stability of the mold shell and is suitable for precision casting of refractory metals such as high-temperature alloys and stainless steel. Detailed Implementation
[0023] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention.
[0024] Furthermore, it should be understood that the one or more method steps mentioned in this invention do not preclude the existence of other method steps before or after the combined steps, or the insertion of other method steps between these explicitly mentioned steps, unless otherwise stated. Moreover, unless otherwise stated, the numbering of each method step is merely a convenient tool for identifying each method step, and not intended to limit the order of the method steps or limit the scope of the invention. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered within the scope of the invention.
[0025] Unless otherwise specified, the experimental conditions used in the examples are generally in accordance with conventional conditions in the art or the conditions recommended by the reagent company. Unless otherwise specified, the materials and reagents used in the examples can be purchased commercially.
[0026] The carboxylated nitrile butadiene latex predispersant (XNBR) used in the various embodiments and comparative examples of the present invention has a solid content of 45% and a pH of 8.0; the styrene-butadiene latex predispersant (SBR) used has a solid content of 50% and a pH of 8.5. Test methods
[0027] Coating viscosity: The viscosity was measured using a Brookfield DV2T rotational viscometer with an LV-4 rotor at 25°C and 60 rpm.
[0028] Coating performance: Apply the coating to the surface of a standard wax model (50mm×30mm×10mm), lift it up and observe the leveling of the coating. Record the time (s) required for the coating surface to return to a smooth, free of flow marks. The shorter the leveling time, the better the coating performance.
[0029] Storage stability: Place the coating in a sealed container, let it stand at 25°C, and observe and record the time when obvious stratification or flocculation occurs.
[0030] Wet flexural strength: Referring to HB 5352.2-2004 "Determination of properties of coatings for investment casting - Part 2: Strength", each layer of coating was applied to a stainless steel sample mold to prepare a single-layer shell sample with dimensions of 120mm×20mm×5mm. After drying to a constant mass at 25℃ and 60% relative humidity, the flexural strength was tested using a universal testing machine with a span of 80mm and a loading rate of 5mm / min.
[0031] High-temperature bending strength: The specimens after the above wet bending strength test were calcined at 1000℃ for 2 hours, cooled in the furnace, and then the bending strength was tested in the same way.
[0032] Interlayer bond strength: A three-layer composite shell sample was prepared by sequentially applying a top layer, a transition layer, and a back layer coating. After complete drying, a universal testing machine was used to test the tensile shear strength between the top layer and the transition layer, and between the transition layer and the back layer, in a direction perpendicular to the layers. The loading rate was 50 mm / min, and the average value was taken.
[0033] Surface roughness Ra: Using investment casting standard sample molds, shells were prepared using the coating systems of each embodiment and comparative example, and ZG230-450 cast steel samples were poured. After cleaning, the surface roughness Ra of the castings was measured using a surface roughness meter.
[0034] Yield: Using the same batch of wax molds (100 pieces each), shells were prepared and cast using the coating systems of each embodiment and comparative example, and the proportion of qualified castings without surface defects, shell peeling, and cracks was counted.
[0035] Air permeability: The air permeability of the back shell sample was determined according to JB / T 4007-2018 "Test Method for Coatings in Investment Casting". Example
[0036] Example 1: Preparation of Layered Coating and Shell Fabrication Layered coating preparation: Topcoat: Take low-sodium silica sol (SiO2 content 30wt%, Na) +1000g of a pre-dispersion of carboxylated nitrile butadiene latex (120ppm content, pH 9.2) was preheated to 40℃. 20g of this pre-dispersion was slowly added dropwise over 20min while stirring at 800rpm. After addition, the mixture was cured at 35℃ for 1.5h, with viscosity measured every 30min. Curing was considered complete when the viscosity increased by 4%. After curing, 3000g of zircon powder (325 mesh), 2g of O-20 wetting agent, and 1g of FA905 defoamer were added. The pH was adjusted to 9.3 with N,N-dimethylethanolamine, and the mixture was stirred for 30min to obtain the topcoat.
[0037] Transition layer coating: Take 1000g of the above-mentioned low-sodium silica sol and preheat it to 40℃. While stirring at 800rpm, first add 20g of styrene-butadiene latex pre-dispersion and stir for 12min. Then, slowly add 11.1g of the above-mentioned carboxylated nitrile butadiene latex pre-dispersion over 15min. After the addition is complete, cure at 35℃ for 2h. Curing is considered complete when the viscosity increase is 3%. After curing, add 1000g of zircon powder (200 mesh), 1500g of mullite powder (200 mesh), 2g of wetting agent O-20, and 1g of defoamer FA905. Adjust the pH to 9.3 and stir for 30min to obtain the transition layer coating.
[0038] Backing Coating: Take 1000g of the above-mentioned low-sodium silica sol and preheat it to 40℃. While stirring at 800rpm, slowly add 48g of the above-mentioned styrene-butadiene latex pre-dispersion solution dropwise over 30min. After the addition is complete, maintain a constant temperature of 35℃ for 2.5h. Curing is considered complete when the viscosity increase is 4%. After curing, add 1000g of mullite powder (100 mesh), 1000g of quartz sand (80 mesh), 2g of wetting agent O-20, and 1g of defoamer FA905. Adjust the pH to 9.3 and stir for 30min to obtain the backing coating.
[0039] Shell preparation: First, a top coat of paint is applied to the surface of the wax model, followed by sprinkling with sand (100-mesh zircon sand), and drying for 4 hours at 25℃ and 60% relative humidity; then, a transition layer of paint is applied, followed by sprinkling with sand (60-mesh mullite sand), and drying for 5 hours; finally, a back coat of paint is applied, followed by sprinkling with sand (40-mesh quartz sand), and drying for 7 hours. The transition layer and back coat are applied three times each to obtain a shell with a total thickness of 8 mm. Example 2
[0040] The difference from Example 1 is that the amount of carboxylated nitrile latex predispersant added to the topcoat is 13.3g (equivalent to 2% of the mass of SiO2 on a dry solid basis), while the rest of the formulation and process are the same as in Example 1. Example 3
[0041] The difference from Example 1 is that the amount of carboxylated nitrile latex predispersant added to the topcoat is 26.7g (equivalent to 4% of the mass of SiO2 on a dry solid basis), while the rest of the formulation and process are the same as in Example 1. Example 4
[0042] The difference from Example 1 is that the amount of styrene-butadiene latex pre-dispersion liquid added to the back coating is 36g (equivalent to 6% of the mass of SiO2 on a dry solid basis), while the rest of the formulation and process are the same as in Example 1. Example 5
[0043] The difference from Example 1 is that the amount of styrene-butadiene latex pre-dispersion liquid added to the back coating is 60g (equivalent to 10% of the mass of SiO2 on a dry solid basis), while the rest of the formulation and process are the same as in Example 1. Example 6
[0044] The difference from Example 1 is that the amount of styrene-butadiene latex predispersant added to the transition layer coating is 15g and the amount of carboxylated nitrile latex predispersant added is 16.7g, that is, the mass ratio of styrene-butadiene to carboxylated nitrile is 1:1 (the total amount added is equivalent to 5% of the mass of SiO2 on a dry solid basis). The rest of the formulation and process are the same as in Example 1. Example 7
[0045] The difference from Example 1 is that the amount of styrene-butadiene latex predispersant added to the transition layer coating is 22.5g and the amount of carboxylated nitrile latex predispersant added is 8.33g, that is, the mass ratio of styrene-butadiene to carboxylated nitrile is 3:1 (the total amount added is equivalent to 5% of the mass of SiO2 on a dry solid basis). The rest of the formulation and process are the same as in Example 1. Example 8
[0046] The difference from Example 1 is that the Na in the low-sodium silica sol + The content is 80 ppm, and the rest of the formula and process are the same as in Example 1. Comparative Example
[0047] Comparative Example 1 The difference from Example 1 is that styrene-butadiene latex is used as the organic reinforcing phase in the top, transition, and back coatings, but the amount added to each layer is set according to the layered gradient of Example 1, that is, 18g of styrene-butadiene latex pre-dispersion liquid (equivalent to 3% of SiO2 mass) is added to the top layer, 30g (equivalent to 5% of SiO2 mass) is added to the transition layer, and 48g (equivalent to 8% of SiO2 mass) is added to the back layer. The remaining conditions are the same as in Example 1.
[0048] Comparative Example 2 The difference from Example 1 is that carboxylated nitrile butadiene latex is used as the organic reinforcing phase in the top, transition, and back coatings, but the amount added to each layer is set according to the layered gradient of Example 1, that is, 20g of carboxylated nitrile butadiene latex pre-dispersion (equivalent to 3% of SiO2 mass) is added to the top layer, 33.3g (equivalent to 5% of SiO2 mass) is added to the transition layer, and 53.3g (equivalent to 8% of SiO2 mass) is added to the back layer. The remaining conditions are the same as in Example 1.
[0049] Comparative Example 3 The difference from Example 1 is that the topcoat, transition layer, and backcoat all use the same compounded latex (styrene-butadiene latex to carboxylated nitrile butadiene latex in a mass ratio of 2:1). The topcoat addition, based on dry solids, is equivalent to 3% of the SiO2 mass (12g of styrene-butadiene latex pre-dispersion and 6.7g of carboxylated nitrile butadiene latex pre-dispersion), the transition layer addition is equivalent to 5% of the SiO2 mass (20g of styrene-butadiene latex pre-dispersion and 11.1g of carboxylated nitrile butadiene latex pre-dispersion), and the backcoat addition is equivalent to 8% of the SiO2 mass (32g of styrene-butadiene latex pre-dispersion and 17.8g of carboxylated nitrile butadiene latex pre-dispersion). All three coatings were prepared using a step-by-step curing process, the same as in Example 1. All other conditions were the same as in Example 1.
[0050] Comparative Example 4 The difference from Example 1 is that no carboxyl-based nitrile latex is added to the topcoat; only low-sodium silicate sol and refractory aggregate are used. All other conditions are the same as in Example 1.
[0051] Comparative Example 5 The difference from Example 1 is that the amount of carboxylated nitrile latex pre-dispersion added to the topcoat is 40g (equivalent to 6% of the mass of SiO2 on a dry solid basis). The rest of the formulation and process are the same as in Example 1.
[0052] Comparative Example 6 The difference from Example 1 is that no styrene-butadiene latex is added to the backing coating; only low-sodium silicate sol and refractory aggregate are used. All other conditions are the same as in Example 1.
[0053] Comparative Example 7 The difference from Example 1 is that the amount of styrene-butadiene latex pre-dispersion added to the back coating is 72g (equivalent to 12% of the mass of SiO2 on a dry solid basis). The rest of the formulation and process are the same as in Example 1.
[0054] Comparative Example 8 The difference from Example 1 is that only styrene-butadiene latex (30g of styrene-butadiene latex pre-dispersion solution, equivalent to 5% of the mass of SiO2 on a dry solids basis) is used in the transition layer coating, and no carboxyl-based nitrile butadiene latex is added. The rest of the formulation and process are the same as in Example 1.
[0055] Comparative Example 9 The difference from Example 1 is that only carboxylated nitrile butadiene latex (33.3g of carboxylated nitrile butadiene latex pre-dispersion solution, equivalent to 5% of SiO2 by dry solids) is used in the transition layer coating, and styrene-butadiene latex is not added. The rest of the formulation and process are the same as in Example 1.
[0056] Comparative Example 10 The difference from Example 1 is that Na is used. + A silica sol with a concentration of 500 ppm (SiO2 content 30 wt%, pH 9.2) was used instead of a low-sodium silica sol. The remaining formulation and process were the same as in Example 1.
[0057] Comparative Example 11 The difference from Example 1 is that Na is used. + A silica sol with a concentration of 1500 ppm (SiO2 content 30 wt%, pH 9.2) was used instead of a low-sodium silica sol. The remaining formulation and process were the same as in Example 1.
[0058] Comparative Example 12 The difference from Example 1 is that Na is used. + A conventional silica sol with a concentration of 2500 ppm (SiO2 content 30 wt%, pH 9.2) was used instead of the low-sodium silica sol. The remaining formulation and process were the same as in Example 1.
[0059] Comparative Example 13 The difference from Example 1 is that the preparation of all three coatings adopts a one-step mixing method, that is, the latex is added to the silica sol at one time, stirred for 30 minutes, and then the refractory aggregate is directly added without a curing step. The rest of the formulation is the same as in Example 1.
[0060] Table 1 records the differences between each embodiment and the comparative example, including the type of latex added to each surface layer, the amount of dry solids added to the latex compared to the mass of silica sol SiO2, and the amount of silica sol Na. + Content and ripening process.
[0061] Table 1. Differences between the Examples and Comparative Examples Performance testing
[0062] The test results of each embodiment and comparative example are shown in Tables 2-6.
[0063] Table 2. Coating performance test results
[0064] Table 3. Test results of shell wet strength and drying performance
[0065] Table 4. Test results of interlayer bonding and casting surface quality
[0066] Table 5 Results of backing layer air permeability and collapse test
[0067] Table 6. High-temperature flexural strength test results (calcined at 1000℃ for 2 hours)
[0068] Results analysis: (1) The effects of the addition amount and ratio of organic reinforcing phases in the surface layer, back layer, and transition layer on the shell performance are shown in Tables 2-5. In the surface layer, increasing the amount of carboxylated nitrile latex from 0% to 6% (Examples 1-3, Comparative Examples 4-5) increased the wet flexural strength from 2.0 MPa to 4.5 MPa, but extended the drying time from 6 h to 5.5 h. After the addition amount exceeded 4%, the coating viscosity increased significantly and the yield decreased, indicating that 2-4% is a suitable range. In the back layer, increasing the amount of styrene-butadiene latex from 0% to 12% (Examples 1, 4-5, Comparative Examples 6-7) increased the wet flexural strength from 2.2 MPa to 5.8 MPa and the air permeability from 6 to 20 cm² / (Pa·min). However, after the addition amount exceeded 10%, the drying time significantly increased and the residual strength after calcination was too low, indicating that 6-10% is a suitable range. When the mass ratio of styrene-butadiene to carboxybutadiene-acrylonitrile in the transition layer was adjusted from 1:1 to 3:1 (Examples 1, 6-7, Comparative Examples 8-9), the interlayer bonding strength reached 2.1 MPa at 2:1. When deviating from this ratio, it dropped to 1.3-1.8 MPa, indicating that (1.5-2.5):1 is a suitable range.
[0069] (2) The necessity of layered differentiated design is shown in Tables 4-5. Comparative Example 1 uses styrene-butadiene latex throughout (with addition amounts in gradients), achieving a surface roughness Ra of 3.8 μm and a yield of 89%; Comparative Example 2 uses carboxylated nitrile butadiene latex throughout, with a back layer air permeability of only 11 cm. 2 / (Pa·min), yield was 86%; Comparative Example 3 used a uniform compound for all layers, with compromises in the performance of each layer, and yielded 91%. The above results are all lower than 95% of Example 1, indicating that simply adjusting the amount added or using a uniform compound cannot replace the targeted matching of latex type and layer function.
[0070] (3) Na in silica sol + The effects of Na content on shell properties are shown in Tables 3, 5, and 6. +As the Na content increased from 80 ppm to 2500 ppm (Examples 1, 8, and Comparative Examples 10-12), the wet flexural strength of the surface layer decreased from 4.0 MPa to 2.6 MPa, the high-temperature flexural strength decreased from 5.5 MPa to 3.5 MPa, and the yield decreased from 96% to 84%. Furthermore, the drying time and coating viscosity increased with increasing Na content. + The increase in content and the lengthening and enlargement indicate that Na + ≤150ppm yields the best overall performance.
[0071] (4) The effects of the stepwise in-situ curing process are shown in Tables 2-4. Comparative Example 13 adopted a one-step mixing method, which significantly increased the viscosity of the coating, reduced the storage stability to only 3 days, decreased the wet flexural strength of the surface layer to 3.0 MPa, reduced the interlayer bonding strength to 1.5 MPa, and the yield was 89%. This shows that stepwise in-situ curing has an important impact on the stability of the coating and the quality of the shell.
[0072] In summary, this invention achieves synergistic improvements in wet strength, drying speed, interlayer bonding, casting surface quality, yield, permeability, collapsibility, and high-temperature strength by differentiating and optimizing the organic reinforcing phases of the surface layer, transition layer, and back layer under the same low-sodium silica sol binder system, and by combining it with a step-by-step in-situ curing process.
[0073] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any form or substance. It should be noted that those skilled in the art can make various improvements and additions without departing from the method of the present invention, and these improvements and additions should also be considered within the scope of protection of the present invention. Any modifications, alterations, and equivalent changes made by those skilled in the art based on the above-disclosed technical content without departing from the spirit and scope of the present invention are equivalent embodiments of the present invention. Furthermore, any modifications, alterations, and evolutions made to the above embodiments based on the essential technology of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A layered coating for precision casting shell making, characterized in that, It includes separately packaged topcoat, transition coat, and backcoat, wherein: The topcoat uses low-sodium silica sol as an inorganic binder and carboxylated nitrile latex as an organic reinforcing phase. The amount of carboxylated nitrile latex added is 2%-4% of the mass of SiO2 in the low-sodium silica sol, based on dry solids. The transition layer coating uses low-sodium silica sol as an inorganic binder and a compound of styrene-butadiene latex and carboxylated nitrile butadiene latex as an organic reinforcing phase. The mass ratio of styrene-butadiene latex to carboxylated nitrile butadiene latex is (1.5-2.5):1, and the total amount added, based on dry solids, is 4%-6% of the mass of SiO2 in the low-sodium silica sol. The back coating uses low-sodium silica sol as an inorganic binder and styrene-butadiene latex as an organic reinforcing phase. The amount of styrene-butadiene latex added is 6%-10% of the mass of SiO2 in the low-sodium silica sol, based on dry solids. Among them, the low-sodium silica sol contains Na + Content ≤150ppm, pH 8.5-10.
5.
2. The layered coating according to claim 1, characterized in that, The pH of the topcoat, transition coat, and backcoat is adjusted to 9.0-9.5 using an organic alkali.
3. The layered coating according to claim 1 or 2, characterized in that, The surface coating also includes zircon powder and / or fused alumina powder as refractory aggregate, with a powder-to-liquid ratio of (2.5-3.5):
1.
4. The layered coating according to claim 1 or 2, characterized in that, The transition layer coating also includes zircon powder and / or mullite powder as refractory aggregate, with a powder-to-liquid ratio of (2.0-3.0):
1.
5. The layered coating according to claim 1 or 2, characterized in that, The backing coating also includes mullite powder and / or quartz sand as refractory aggregate, with a powder-to-liquid ratio of (1.5-2.5):
1.
6. The layered coating according to claim 1 or 2, characterized in that, The carboxylated nitrile butadiene latex has a solid content of 40-50% and a pH of 7.5-8.5; the styrene-butadiene latex has a solid content of 45-55% and a pH of 8.0-9.
0.
7. A method for preparing a layered coating as described in any one of claims 1-6, characterized in that, Includes the following steps: Topcoat pre-preparation: Preheat low-sodium silica sol to 35-45℃, and slowly add carboxylated butadiene-acrylonitrile latex pre-dispersion solution while stirring, with the addition time controlled at 15-30 min; after the addition is completed, keep it at 30-40℃ for 1-2 h for curing; after curing, add refractory aggregates and additives, and adjust the pH to 9.0-9.5; Pre-preparation of transition layer coating: Preheat low sodium silica sol to 35-45℃, first add styrene-butadiene latex pre-dispersion, stir for 10-15 min, then slowly add carboxyl butadiene nitrile latex pre-dispersion, controlling the adding time to 10-20 min; After the addition is complete, maintain a constant temperature of 30-40℃ for 1.5-2.5 hours; after maturation, add refractory aggregates and additives, and adjust the pH to 9.0-9.
5. Backing coating pre-preparation: Preheat low-sodium silica sol to 35-45℃, and slowly add styrene-butadiene latex pre-dispersion liquid while stirring, with the addition time controlled at 20-40 min; after the addition is completed, keep it at 30-40℃ for 2-3 h for curing; after curing, add refractory aggregates and additives, and adjust the pH to 9.0-9.
5.
8. The preparation method according to claim 7, characterized in that, During the pre-preparation of the topcoat, transition coat, and backcoat, the stirring rate is 500-1500 rpm.
9. A method for preparing a precision casting mold shell, characterized in that, The layered coating described in any one of claims 1-6 is used to sequentially coat a top layer, a transition layer, and a back layer. After each layer is coated, refractory sand is sprinkled on and the coating is dried. The drying time for the top layer is 4-6 hours, the drying time for the transition layer is 5-7 hours, and the drying time for the back layer is 6-8 hours.
10. A precision-cast shell, obtained by the method of claim 9.
Citation Information
Patent Citations
New method for manufacturing composite coating shell for precisely casting fusible patterns
CN101642798A
A surface coating for precision casting shell making and its preparation method
CN105108053B
A transition layer coating for precision casting shell making and its preparation method and application
CN105108054B
Investment casting compositions, molds and related methods
CN106232261B
Organic reinforcing agent for modified precision casting silica sol
CN111790881A
